Ulocladium gpagarwalii and U. lignicola two new sp. nov. from Andhra Pradesh - C. MANOHARACHARY1*; D.K. AGARWAL2, D. NAGARAJU1, I.K. KUNWAR1, (Indian Phytopathology, 2009)
Survey of microfungi from Khammam forest, Andhra Pradesh, yielded two novel anamorphic dematiaceous hyphomycetous fungi belonging to the genus Ulocladium Preuss. These fungi differ from the documented species of Ulocladium, hence described as new species viz. Ulocladium gpagarwalii sp. nov. and Ulocladium lignicola sp. nov.